Motor imagery has a priming effect on motor execution in people with multiple sclerosis - Tacchino, Andrea; Pedullà, Ludovico; Podda, Jessica; Monti Bragadin, Margherita; Battaglia, Mario Alberto; Bisio, Ambra; Bove, Marco; Brichetto, Giampaolo (Frontiers in Human Neuroscience, 2023)
Priming is a learning process referred to behavioural changes caused by a previous exposure to a similar stimulus. Motor imagery (MI), the action representation rehearsal within the working memory without engaging actual execution, could be a strategy for priming motor system. This study investigates if MI primes action execution in Multiple Sclerosis (MS). Here, 17 people with MS (PwMS) and 19 healthy subjects (HS), all right-handed and good-imaginers, performed as accurately and quickly as possible, with a pencil, actual or mental pointing movements between targets of small (1.0×1.0 cm) or large (1.5×1.5 cm) size. In actual trials, they completed five actual cycles of pointing between the left and right targets, whereas in mental trials, the first four cycles were imagined whereas the fifth was actually executed. The fifth cycle was introduced to assess the MI priming effect on actual execution. All the conditions, randomly presented, were performed with both dominant (i.e. right) and non-dominant arms. The analysis of the duration of the first four cycles in both actual and mental trials confirmed previous findings, showing isochrony in HS with both arms and significantly faster mental than actual movements (anisochrony) in PwMS (p<0.01) (time (s); HS right: actual: 4.23±0.15, mental: 4.36±0.16; left: actual: 4.32±0.15, mental: 4.43±0.18; PwMS right: actual: 5.85±0.16, mental: 5.99±0.21; left: actual: 6.68±0.20, mental: 5.94±0.23); anisochrony in PwMS was present when the task was performed with the non-dominant arm. Noteworthy, the temporal analysis on the fifth actual cycle showed no differences between actual and mental trials for HS with both arms, whereas in PwMS the fifth actual cycle after the four mental cycles was significantly faster than after the four actual cycles for the non-dominant arm (p<0.05) (time (s); HS right: actual: 1.03±0.04, mental: 1.03±0.03; left: actual: 1.08±0.04, mental: 1.05±0.03; PwMS right: actual: 1.48±0.04, mental: 1.48±0.06; left: actual: 1.66±0.05, mental: 1.48±0.06). These results seem suggesting that few mental repetitions of an action could be sufficient to exert a priming effect on the actual execution of the same action in PwMS. It would suggest to furtherly investigate the potential use of MI as a new motor-cognitive tool for MS neurorehabilitation.